2018
DOI: 10.21608/ejh.2018.13840
|View full text |Cite
|
Sign up to set email alerts
|

Wheat germ oil attenuates deltamethrin-induced injury in rat cerebellar cortex: Histological and immunohistochemical study

Abstract: Introduction: Deltamethrin, a widely used insecticide, has neurotoxic effects causing apoptosis. Wheat germ oil is a highly valuable part of wheat that proved to have neuro-protective and anti-apoptotic effects. Aim of the work: To evaluate the possible protective role of wheat germ oil in deltamethrin-induced injury in rat cerebellar cortex. Materials and Methods: Four equal groups of adult male albino rats "10 rats, each" were used; control group, wheat germ oil (WGO) group (100 mg/kg), deltamethrin group (0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Regarding the cytoplasmic immune reaction of the GFAP in the astrocyte cell body and the processes thereof, there was a significant increase in contrast with the sham control group in the MCAO rats. GFAP is the mature astrocyte intermediate filament; after, it is known as specific astrocyte markers [ 31 ]. Published investigations suggested that any degenerative brain injury could trigger the proliferation of astrocytes and hypertrophy, resulting in severe astrogliosis with increased GFAP positive reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the cytoplasmic immune reaction of the GFAP in the astrocyte cell body and the processes thereof, there was a significant increase in contrast with the sham control group in the MCAO rats. GFAP is the mature astrocyte intermediate filament; after, it is known as specific astrocyte markers [ 31 ]. Published investigations suggested that any degenerative brain injury could trigger the proliferation of astrocytes and hypertrophy, resulting in severe astrogliosis with increased GFAP positive reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the sections were stained with a diaminobenzidine chromogen kit (Beyotime Biotechnology Co, LTD.) and then counterstained with Mayer's haematoxylin, dehydrated, cleared by xylene and covered. Non-immune serum was used in place of the primary antibodies in negative control sections 20 . Under a light microscope, the sections were examined at Human Anatomy and Embryology Department, Faculty of Medicine, Assiut University, Assiut- Egypt.…”
Section: Methodsmentioning
confidence: 99%